Pregnancy and humoral immune response in mice chronically infected by Trypanosoma cruzi. - Carlier, Y (1987)
The effect of pregnancy on the humoral immune response induced by Trypanosoma cruzi was studied in groups of chronically infected and pregnant mice (IP) or chronically infected and nonpregnant mice (INP) of strain BALB/c. Groups of noninfected and nonpregnant mice (NINP) or noninfected and pregnant mice (NIP) served as controls. The pregnant mice were killed on day 17 of pregnancy. Anti-T. cruzi immunoglobulin G (IgG) and IgM antibodies, detected by immunofluorescence or enzyme-linked immunosorbent assay or both, underwent a pregnancy-associated decrease of 20 to 40%, whereas complement-mediated lytic antibodies were unaffected by pregnancy. Immunoblotting analysis indicated identical specificities of the anti-T. cruzi antibodies in IP and INP groups. The levels of all the immunoglobulin isotypes (particularly IgG2a and IgG3), circulating immune complexes, rheumatoid-like factor, and anti-DNA antibodies were considerably increased during chronic infection (NINP versus INP), which could be related to the high degree of polyclonal B-cell activation occurring in T. cruzi infection. However, pregnancy significantly decreased (by 20 to 60%) such parameters. IgG levels were particularly affected (by 40 to 60%), and the decreases could be ordered as follows: IgG3 greater than IgG2a greater than IgG1 greater than IgG2b for IP versus INP. Comparisons between the noninfected groups indicated differences only in IgG levels. These results indicate the following. (i) The specific humoral anti-T. cruzi immune response is weakly affected by pregnancy, which is not sufficient to modify the course of the mother's infection. (ii) Pregnancy does not modify the expression of the anti-T. cruzi antibody repertory. (iii) Pregnancy reduces the polyclonal B-cell activation, particularly the levels of the IgG isotypes undergoing the greatest activation.